INTERAKSI SOSIAL PEDAGANG KAKI LIMA DI PASAR PUAN MAIMUN KABUPATEN KARIMUN KEPULAUAN RIAU - Megawati "; Syafrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This thesis submitted in order to quality a sociology bachelors degree with the title “ Social Interaction Street Vendors In Puan Maimun Market Karimun Regency, Riau Archipelago. To findout how the social interaction that occur betwee the street vendors, factor that affect the creation of social interaction that take place and interwoven between street vendors in Puan Maimun market, Karimun Regency, the author conducted data collection using observation techniques and in depth interviews with respondents. As for how sampling or respondents is done by simple random sampling techniques (in a random way) that has came chance and opportunity to be selected as a samples, the samples 15 street vendors respondents specified of the total population 129 merchant. The teory used in this reasearch is the theory of social interaction and the structural-functional theory. The method used is qualitative descriptive. Result of research conduted in general, the author say that the high familiar relationships that occur between them. Social interactions that occur make a trader to another may affect each other. The social interaction resulted in relationships that is both negative and positive. Tolarance among street vendors Puan Maimun Market that made them closer. A sense of togetherness between cadger that make harmony among them better. The results show that social interaction that exist between good cadger.Key words : Social Interaction, Cadger